Experience and reflection: curriculum units to develop generic skills in speech and language therapy students - Germano, Helena (2018)
The Speech and Language Therapy (SLT) program (Instituto Politécnico de Setúbal, Portugal) integrates a domain of personal and professional development since the implementation of Bologna process. This domain includes nine curriculum units called Experience and Reflection (ER), with 54 hours each (25 contact hours). ER intends to develop generic competences that allow students to integrate forms of relationship relevant for the clinical dimension of Speech Therapy and to know how to avoid risk situations for themselves and others. ER was created based on the following theoretical frameworks: intrapersonal and interpersonal intelligence (Gardner, 1983); Empowerment in education - critical thinking (Harvey, 2004); Reflection (Law et al, 2007); Tutoring and Mentoring; Double loop learning (Brockbank & McGill, 2006). This set of 9 Curriculum units has subject specific topics (eg. communication styles, clinical interview, diversity, team work, attending families, reflection on clinical practice) through which generic skills are developed: self-knowledge, time management, assertiveness, creativity, cooperation, leadership, resilience, to manage situations of change, attending the other, counseling, to manage diversity, contacts network. The objective of this work is to analyze the perspective of students about ER and their self-assessment on generic skills acquired along the 9 ER. Method: Data was gathered in 3 different academic years: 2013, 2014 and 2016. In 2013, 14 students performed a reflection focusing on the topics: relevance in the academic curriculum; what represented to me; competences fully developed and under development. In 2014, students filled a self-assessment questionnaire based on the competences defined by NetQues-CPLOL to a newly graduated speech and language therapist (generic competences included). They graded each question with a likert scale from 1 to 5 where 1=not acquired and 5=completely acquired. In 2016 students filled the same questionnaire and reply to open questions asking a reflection on the same 3 topics asked in 2013. A content analysis of the qualitative data was performed, and the results of the questionnaire were analyzed. Results: Through the content analysis, major themes observed were: development of personal and professional skills (e. g. self-awareness, critical thinking, management of unexpected situations, humanity in health care, active learning, constructive self-assessment), initial misunderstanding of the utility of ER, full understanding when at stage, relevance for academic curriculum, teaching methodology. The self-assessment of generic competencies was equivalent in both years with mean values between 4 and 5. Conclusions: The positive evaluation of students demonstrated that the objectives of ER were met. It is evident that the generic skills are perceived as acquired and as essential for quality professional practice. The teaching methodology is considered appropriate and relevant for students, as they could “transform teaching and learning in an active process for understanding” (Harvey, 2004). We can conclude that the existence of ER in the curriculum is relevant and differentiating.